The mulatta and the politics of race - Zackodnik, Teresa C. (Jackson : University Press of Mississippi, 2004)
From abolition through the years just before the civil rights struggle began, African American women recognized that a mixed-race woman made for a powerful and, at times, very useful figure in the battle for racial justice. The Mulatta and the Politics of Race traces many key instances in which black women have wielded the image of a racially mixed woman to assault the color line. In the oratory and fiction of black women from the late 1840s through the 1950s, Teresa C. Zackodnik finds the mulatta to be a metaphor of increasing potency. Before the Civil War white female abolitionists created th.
Acknowledgments; Introduction; 1. Fixing the Color Line: The Mulatta, American Courts, and the Racial Imaginary; 2. "White Slaves" and Tragic Mulattas: The Antislavery Appeals of Ellen Craft and Sarah Parker Remond; 3. Little Romances and Mulatta Heroines: Passing for a "True Woman" in Frances Harper's Iola Leroy and Pauline Hopkins's Contending Forces; 4. Commodified "Blackness" and Performative Possibilities in Jessie Fauset's: The Chinaberry Tree and Nella Larsen's Quicksand.
Includes bibliographical references (pages 217-227) and index.
Print version record.
JSTOR
Keywords: American fiction -- African American authors -- History and criticism; Race in literature; American fiction -- Women authors -- History and criticism; Political fiction, American -- History and criticism; African American women -- Intellectual life; Politics and literature -- United States; Women and literature -- United States; Multiracial people in literature; Race relations in literature; Racism in literature; Women in literature; Roman américain -- Auteurs noirs américains -- Histoire et critique; Race dans la littérature.; Politique-fiction américaine -- Histoire et critique; Noires américaines -- Vie intellectuelle; Politique et littérature -- États-Unis.; Femmes et littérature -- États-Unis.; Relations raciales dans la littérature.; Racisme dans la littérature.; Femmes dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- American -- African American; African American women -- Intellectual life; American fiction -- African American authors; American fiction -- Women authors; Political fiction, American; Politics and literature; Race in literature; Race relations in literature; Multiracial people in literature; Racism in literature; Women and literature; Women in literature; United States; Criticism, interpretation, etc